Dispute over the Existence of the World and the Work of Art - Grygorczuk, Victoria (Sensus Historiae, 2023)
In this paper we propose to carry out a comparative study of Edmund Husserl’s image theory and the theory of the pictorial work of art by the Polish phenomenologist Roman Ingarden. This study will be carried out from the idealism-realism polemic between both authors. Our purpose is to demonstrate the existence of a clear parallelism between the aesthetic theory of each of the authors and the general idealism-realism dispute between them, as well as to point out that the same controversy can be understood from Ingarden’s theory of the purely intentional object.